The polytrauma patient: Current concepts and evolving care - Christopher Lee, MD; Todd E. Rasmussen, MD; Hans-Christoph Pape, MD; Joshua L. Gary, MD; James P. Stannard, MD; Justin M. Haller, MD (OTA International, 2021)
Abstract. Principles of care in the polytraumatized patient have continued to evolve with advancements in technology. Although hemorrhage has remained a primary cause of morbidity and mortality in acute trauma, emerging strategies that can be applied pre-medical facility as well as in-hospital have continued to improve care. Exo-vascular modalities, including the use of devices to address torso hemorrhage and areas not amenable to traditional tourniquets, have revolutionized prehospital treatment. Endovascular advancements including the resuscitative endovascular balloon occlusion of the aorta (REBOA), have led to dramatic improvements in systolic blood pressure, although not without their own unique complications. Although novel treatment options have continued to emerge, so too have concepts regarding optimal time frames for intervention. Though prior care has focused on Injury Severity Score (ISS) as a marker to determine timing of intervention, current consensus contends that unnecessary delays in fracture care should be avoided, while respecting the complex physiology of certain patient groups that may remain at increased risk for complications. Thromboelastography (TEG) has been one technique that focuses on the unique pathophysiology of each patient, providing guidance for resuscitation in addition to providing information in recognizing the at-risk patient for venous thromboembolism. Negative pressure wound therapy (NPWT) has emerged as a therapeutic adjuvant for select trauma patients with significant soft tissue defects and open wounds. With significant advancements in medical technology and improved understanding of patient physiology, the optimal approach to the polytrauma patient continues to evolve.